Role playing games and emotions in dispute resolution environments - Carneiro, Davide Rua (2011)
Electronic contracting, mostly through software agents, led to an impressive growth in electronic transactions, but also in the number of disputes arising out of these transactions. Paper-based courts are however unable to efficiently deal with this increase in disputes. On the other hand, current Online Dispute Resolution methodologies are impersonal and cold, leaving aside important information such as the disputants’ body language and emotions. In that sense, in this paper we propose the creation of environments for dispute resolution that can complement the existing tools with important context information. This, we believe, will lead to dispute resolution tools that will more efficiently achieve mutually satisfactory outcomes.